ANALYSIS OF FACTORS RELATED TO THE COMPLETENESS OF TETANUS TOXOID IMMUNIZATION IN TRIMESTER III PREGNANT WOMEN - Anita Nofita Sari; Tini Tini; Lidia Lushinta (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Tetanus toxoid immunization in third trimester pregnant women is very important to prevent the risk of tetanus infection in newborns. Most cases of neonatal death in developing countries are due to tetanus, and neonatal tetanus is the second leading cause of death worldwide in diseases that can be prevented through vaccination. The purpose of this study was to determine the factors associated with the completeness of Tetanus Toxoid immunization in third trimester pregnant women. This study employed an analytical cross-sectional observational design on pregnant women in the third trimester (n=47) at Puskesmas Karangan in 2023. A total sampling method was used, resulting in a sample of 47 infants. Data collection instruments included questionnaires (primary data) and the PWS KIA book (secondary data). The variables examined were immunization completeness (dependent variable) and knowledge, attitude, and spousal support (independent variables). Data were analyzed using the Chi Square test. The results of univariate analysis showed that the majority of respondents with incomplete TT immunization were 24 (51.1%). The results of the bivariate analysis found a relationship between knowledge and P Value (0.004), mother's attitude P Value (0.025) and husband's support P Value (0.029) with the completeness of Tetanus Toxoid immunization in third trimester pregnant women with a value of α = 0.05. The study highlights the strong influence of maternal knowledge on the completeness of Tetanus Toxoid immunization in pregnant women in the third trimester (P-value=0.004), which is more significant compared to maternal attitude and spousal support. Enhancing maternal knowledge regarding TT immunization is crucial in improving immunization coverage and reducing the risk of tetanus infection in newborns.